GENDER STRATEGIES AND POLITICAL LEADERSHIP - N. V. Кhamitov; D. D. Dandekar (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The purpose of the article is to understand the issue of gender strategies of political leadership. Theoretical basis. The works of Ukrainian and foreign scholars helped to find out the specifics of male and female leadership. The article applied the latest methodology of androgyny-analysis. According to this methodology, sex has not only a biological, psychological and social, but also an existential dimension. So, the existential dimension of gender is soulfulness as an existential femininity and spirituality as an existential masculinity. These two beginnings may conflict and may be in harmony. Depending on this, we have constructive or destructive strategies for the development of both the personality and the relations between individuals. Constructiveness here means not only gender equality, but also gender partnership. Originality. In the context of modern gender anthropology and androgyny-analysis, it is found that as a result of the implementation of the strategy of existential sexism and existential hermaphroditism, political leadership becomes authoritarian, and sometimes also totalitarian, while the strategy of androgynism associated with gender partnership gives rise to constructive political leadership. Conclusions. Androgynous personality of a political leader, which balances the existential and psychological qualities of men and women, is able to reform the society and change the country for better.